2006
DOI: 10.2214/ajr.05.0584
|View full text |Cite
|
Sign up to set email alerts
|

Gadobenate Dimeglumine-Enhanced Liver MRI as the Sole Preoperative Imaging Technique: A Prospective Study of Living Liver Donors

Abstract: OBJECTIVE. The objective of our study was to determine whether gadobenate dimeglumine-enhanced MRI is practical as the sole preoperative imaging technique for the examination of living liver donors.SUBJECTS AND METHODS. Forty-four consecutive living donor candidates underwent liver MRI on a 1.5-T MR unit. The MR examination included in-and opposed-phase T1-weighted gradient-echo imaging, T2-weighted MR cholangiography, MR angiography (MRA) and parenchymal phase imaging after the administration of gadobenate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
1
45
1
Order By: Relevance
“…Because it is taken up by functioning hepatocytes and excreted in bile, use of gadobenate dimeglumine results in marked and prolonged enhancement of normal liver parenchyma for as long as 2 hours on T1-weighted images with minimal or no enhancement of nonhepatocellular tumors, improving the utility of MRI in characterizing focal liver lesions [21][22][23]. In addition, several studies have shown successful use of gadobenate dimeglumine in MR angiography of a variety of vascular territories and in MRI of the brain [24][25][26].…”
Section: Choi Et Almentioning
confidence: 99%
“…Because it is taken up by functioning hepatocytes and excreted in bile, use of gadobenate dimeglumine results in marked and prolonged enhancement of normal liver parenchyma for as long as 2 hours on T1-weighted images with minimal or no enhancement of nonhepatocellular tumors, improving the utility of MRI in characterizing focal liver lesions [21][22][23]. In addition, several studies have shown successful use of gadobenate dimeglumine in MR angiography of a variety of vascular territories and in MRI of the brain [24][25][26].…”
Section: Choi Et Almentioning
confidence: 99%
“…Contrast-enhanced magnetic resonance cholangiography (MRC) using hepatobiliary contrast agents, in combination with T1-weighted two-dimensional (2D) or threedimensional (3D) gradient-echo (GRE) sequences, is considered an alternative to conventional techniques for the evaluation of the biliary tree [1,2]. Recent studies have shown that contrast-enhanced MRC is particularly useful for the evaluation of biliary tract abnormalities in healthy individuals (e.g., potential living liver donors), and in patients suspected to have a biliary leak [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that contrast-enhanced MRC is particularly useful for the evaluation of biliary tract abnormalities in healthy individuals (e.g., potential living liver donors), and in patients suspected to have a biliary leak [1,[3][4][5]. Although contrast-enhanced MRC is increasingly used by radiologists, there is paucity of data in the literature with regard to the degree and extent of biliary excretion of hepatobiliary contrast agents.…”
Section: Introductionmentioning
confidence: 99%
“…This contrast agent combines the properties of a gadolinium-based extracellular contrast agent as a hepatocyte-direct excreted at about 2%-4% through the biliary tract. An et al (25) have described an accuracy of 75% with MR cholangiography T2-weighted sequences, 79% with paramagnetic contrast-enhanced T1-weighted sequences, and an increase to 92% in accuracy with the evaluation by means of a combination of both methods.…”
Section: Discussionmentioning
confidence: 99%